Formulation, Optimization, and Evaluation of Ketoconazole Loaded Nanostructured Lipid Carrier Gel for Topical Delivery - Ranpise, Hemant A.; Gujar, Kishore N.; Pawar, Sachin C.; Awasthi, Rajendra; Dua, Kamal; Mathure, Dyandevi; Madan, Jyotsana R. (Drug Delivery Letters, 2020)
Objective: Ketoconazole is used in the treatment of superficial and systemic fungal infections. It acts by blocking the synthesis of ergosterol, an essential component of the fungal cell membrane. The purpose of this work was to formulate ketoconazole loaded nanostructured lipid carriers formulation for skin targeting to minimize the adverse side effects and to prolong release. Methods: The ketoconazole loaded nanostructured lipid carriers were optimized using 32 factorial design to evaluate the effects of process and formulation variables. The nanostructured lipid carriers were prepared by melt-dispersion ultra-sonication method. The formulations were finally incorporated into polymeric gels of Carbopol 940 for convenient application. The gels were evaluated comparatively with commercially available formulations of ketoconazole with respect to ex vivo skin permeation and deposition study on human cadaver skin. Results: Nanostructured lipid carriers showed average particle size, zeta potential, and percentage entrapment in the range of 125.8 ± 1.8 to 295.0 ± 3.8 nm, -13.2 ± 1.1 to -30.9 ± 2.2 mV, and 69.47 ± 2.8 to 95.49 ± 4.5, respectively. Thermal studies revealed no drug-excipient incompatibility and amorphization of ketoconazole. Ex vivo study of the gel exhibited prolonged drug release up to 12 h. In vitro drug deposition study showed that the gel formulation can avoid the systemic uptake, better accumulative uptake of the drug, and nonirritant to the skin compared to marketed formulation. Optimized formulation exhibited better antifungal activity when compared to ketoconazole loaded gel and marketed cream (Keto ® cream). Histolopathology results indicated no toxic effect on the skin. Conclusions: These results indicate that developed nanostructured lipid-carriers gel formulation represents a promising carrier for topical delivery of ketoconazole, having controlled drug release, and potential of skin targeting.
Keywords: nanocarriers